Immediate implant placement and provisionalization: Aesthetic outcome 1 year after implant placement. A prospective clinical multicenter study. (28th January 2020) - Groenendijk, Edith; Staas, Tristan Ariaan; Bronkhorst, Ewald; Raghoebar, Gerry Max; Meijer, Gert Jacobus
Abstract: Background: Prospective aesthetic outcomes on a high number of patients after immediate implant placement and provisionalization (IIPP) are lacking. Purpose: To analyze the aesthetic outcome after IIPP. Materials and Methods: One hundred consecutive patients with a failing maxillary incisor were provided with an immediately placed and provisionalized nonloaded implant using a flapless procedure and palatal implant positioning. The remaining gap buccally was filled with a bone substitute. Preoperatively (T0), 2 weeks postoperatively (T1), direct after placement of the permanent crown (T2), and 1 year after IIPP (T3), standardized light photographs were made. Change in aesthetic score was the primary outcome measure. Both the white aesthetic score (WES) and pink aesthetic score (PES) were used. Results: In the first year postsurgery, the mean total‐WES and total‐PES scores raised from 4.5 to 8.2, and from 9.9 to 12.1, respectively. The mean PES scores for mesial and distal papilla, soft tissue marginal level, contour, color, and texture, raised significantly ( P  < .05), while the alveolar process contour, on average, remained stable from T0 to T3. Conclusions: Within the limitations of this 1‐year research, it may be concluded that, following this minimal invasive IIPP procedure, a high aesthetic outcome was achieved.